The Impact of Knowledge on the Care of the External Genital Area in Adolescent Girls at SMK N "X" in South Jakarta - Dian Anggraini (Journal of Global Research in Public Health, 2022)
Cases of reproductive health problems in adolescents are still found, this is influenced by several factors, one of which is the lack of knowledge and motivation of adolescents to maintain reproductive health. The aim of the research was to identify the knowledge and practice of caring for the external genital area in female adolescents and to identify the results of the analysis of the relationship between knowledge and care for the external genital area in adolescents. Analytical descriptive research methods with a cross sectional approach. Take measurements on each variable at the same time. The sampling technique is the total sample. The Pearson Chi-square test, an alpha value of 0.05, and a 95% confidence interval (CI) were used to analyze the data using the SPSS version 24 program. According to the study's findings, the average knowledge of young women was good (74.8%) and poor (24.2%).The average implementation of treatment for the external genitalia area in young women is routinely done (75.8%) and rarely done (24.2%). With a p value of 0.05, there is a significant relationship between knowledge and care of the external genitalia area in young women.The results of the analysis of knowledge on young women have a significant relationship with the treatment of the external genitalia area, with a p value <0.05 (α 0.05). There is a significant relationship between knowledge and care of the external genital area in young women with a p value <0.05 (α 0.05). The results of the analysis of knowledge on young women have a significant relationship with the treatment of the external genitalia area, with a p value <0.05 (α 0.05). The role of the family to supervise and support the implementation of reproductive health programs in adolescents is very much needed, as well as the role of health workers in providing health education and promotion to increase the motivation of adolescents in maintaining the health of the reproductive organs.